The Position of the Marriage Covenant in Positive Law and Islamic Law - Jamillah, Jamillah (International Asia Of Law and Money Laundering, 2024)
This study was to determine and analyze the position and legal consequences of marriage agreements in positive law in Indonesia the method of this study is normative jurisprudence that examines the legal regulations through a literature study which is then analyzed and described in the results of research the results of the study revealed that the agreement made before marriage has a position that the, and KompilasiHukum Islam, this marriage agreement is made for the sake of legal protection of the property of each, husband or wife.As a result of the law of the marriage agreement on marital property, the togetherness of marital property is limited in accordance with the marriage agreement, in addition to the existence of legal protection against the ownership of property in marriage for the husband or wife, the marriage agreement must not violate or conflict with public order, morality, law and religion. The marriage contract is valid at the time or since the marriage took place. The agreement in principle should not be changed after the marriage took place.